Associations of baseline patient‐reported outcomes with treatment outcomes in advanced gastrointestinal cancer. Issue 4 (10th November 2020) - van Seventer, Emily E.; Fish, Madeleine G.; Fosbenner, Kathryn; Kanter, Katie; Mojtahed, Amirkasra; Allen, Jill N.; Blaszkowsky, Lawrence; Clark, Jeffrey W.; Dubois, Jon; Franses, Joseph W.; Giantonio, Bruce J.; Goyal, Lipika; et al.
Abstract : Background: Patient‐reported outcomes (PROs) assessing quality of life (QOL) and symptom burden correlate with clinical outcomes in patients with cancer. However, to the authors' knowledge, data regarding associations between PROs and treatment response are lacking. Methods: The authors prospectively approached consecutive patients with advanced gastrointestinal cancer who were initiating a new treatment. Prior to treatment, patients reported their QOL (Functional Assessment of Cancer Therapy‐General [FACT‐G], 4 subscales: Functional, Physical, Emotional, Social; higher scores indicate better QOL) and symptom burden (Edmonton Symptom Assessment System [ESAS], Patient Health Questionnaire‐4 [PHQ‐4]; higher scores represent greater symptoms). Regression models were used to examine associations of baseline PROs with treatment response (clinical benefit or progressive disease [PD] at time of first scan), healthcare utilization, and survival. Results: From May 2019 to April 2020, a total of 112 patients with advanced gastrointestinal cancer were enrolled. For treatment response, 64.3% had CB and 35.7% had PD. Higher baseline ESAS‐Physical (odds ratio, 1.04; P = .027) and lower FACT‐G Functional (odds ratio, 0.92; P = .038) scores were associated with PD. Higher ESAS‐Physical (hazard ratio [HR], 1.03; P = .044) and lower FACT‐G Total (HR, 0.96; P = .005), FACT‐G Physical (HR, 0.89; P < .001), and FACT‐G Functional (HR, 0.87; P < .001) scores were associated with a greater hospitalization risk. Lower FACT‐G Total (HR, 0.96; P = .009) and FACT‐G Emotional (HR, 0.86; P = .012) scores as well as higher ESAS‐Total (HR, 1.03; P = .014) and ESAS‐Physical (HR, 1.04; P = .032) scores were associated with worse survival. Conclusions: Baseline PROs are associated with treatment response in patients with advanced gastrointestinal cancer, namely physical symptoms and functional QOL, in addition to health care use and survival. The findings of the current study support the association between PROs and important clinical outcomes, including the novel finding of treatment response. Abstract : In the current study, the authors investigate associations between patient‐reported outcomes (PROs), health care use, and clinical outcomes in a prospectively enrolled cohort of patients with advanced gastrointestinal cancer. Baseline PROs are associated with important clinical outcomes, including the novel finding of treatment response, in patients with advanced gastrointestinal cancer.